A Critical Investigation on Weld Bead Defect Detection System Using IoT (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Welding is a process of joining two metals under the application of heat. During the weldingprocess, there is a chance for the occurrence of an undesired irregularity in the form of adefect. Detection of defects formed during Welding is crucial. Under service conditions,these defects lead to the failure of structures and loss of property. Nowadays there istremendous growth in the field of Internet-of-things. It has many advantages and created agreat effect in the manufacturing Industry. By using the Internet-of-Things (IoT) theinspection is done without human intervention and can monitor the defects of weld using thesensors, analyzing and uploading the data into the cloud and visualizing it in the web on anydevice, anytime, anywhere. The implementation of IoT in welding for weld bead defectdefection decreased the inspection time thereby increased production. By analyzing the datathrough the Internet-of-things the process is automated and can identify the defects usingdifferent sensors for measuring the various performance parameters that govern the weldbead quality. This paper describes the various sensing methods based on infrared,radiography, vision, Ultrasonic, acoustic, spectrography techniques and analyzing the dataobtained from the sensors, and visualizing the data onto the Thing Speak website by sendingit to Cloud using the Internet-of-Things. The weld bead defect detection using IoT can beimplemented in the Manufacturing Industry for real-time weld defect monitoring during thewelding process.